2021
DOI: 10.7716/aem.v10i2.1440
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid GA/GE Beamforming Technique for Side Lobe Cancellation of Linear Antenna Arrays

Abstract: Side lobe level reduction is one of the most critical research topics in antenna arrays beamforming as it mitigates the interfering and jamming signals. In this paper, a hybrid combination between the Genetic algorithm (GA) optimization technique and the gauss elimination (GE) equation solving technique is utilized for the introduction of the proposed GA/GE beamforming technique for linear antenna arrays. The proposed technique estimates the optimum excitation coefficients and the non-uniform inter-elements sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The simulations revealed that the proposed array provided significantly reduced SLL compared to the slot array with a uniform offset location. In [20], a hybrid beamforming technique based on the combination of the genetic algorithm and the Gauss elimination algorithm denoted as GA/GE has been introduced for a specific side lobe cancellation of LAAs that reduces the received interference in the appropriate directions, which improves the receiver sensitivity. However, the GA/GE did not result in a general decrease in SLL.…”
Section: Introductionmentioning
confidence: 99%
“…The simulations revealed that the proposed array provided significantly reduced SLL compared to the slot array with a uniform offset location. In [20], a hybrid beamforming technique based on the combination of the genetic algorithm and the Gauss elimination algorithm denoted as GA/GE has been introduced for a specific side lobe cancellation of LAAs that reduces the received interference in the appropriate directions, which improves the receiver sensitivity. However, the GA/GE did not result in a general decrease in SLL.…”
Section: Introductionmentioning
confidence: 99%